Anti-Tumor Activity and Safety of Multikinase Inhibitors in Advanced and/or Metastatic Thyroid Cancer: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Tsoli, Marina; Alexandraki, Krystallenia I.; Spei, Maria-Eleni; Kaltsas, Gregory A.; Daskalakis, Kosmas (Hormone and Metabolic Research, 2020)
Many trials have demonstrated prime antitumor activity of novel, small molecule multikinase inhibitors (MKIs) in advanced and/or metastatic thyroid cancer (TC). In this work, the PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Web of Science, SCOPUS, and clinicaltrials.gov databases were searched. Quality/risk of bias were assessed using GRADE criteria. Randomized clinical trials (RCTs) comparing two or more systemic therapies in patients with advanced and/or metastatic thyroid cancer were assessed. A total of 1347 articles and 548 clinical trials in clinicaltrials.gov were screened. We included seven relevant RCTs comprising 1934 unique patients assigned to different MKIs. Two separate network meta-analyses included four RCTs in radioiodine refractory well-differentiated thyroid cancer (RR-WDTC) and three RCTs in medullary thyroid cancer (MTC), respectively; all with a low risk of bias. We identified three therapies for RR-WDTC: sorafenib [disease control rate (DCR) odds ratio (OR): 0.11 (95% CI: 0.03–0.40); progression-free survival (PFS) hazard ratio (HR): 1.99 (95% CI: 1.62–2.46)], vandetanib [DCR_OR:0.26 (95% CI: 0.06–1.24); PFS_HR: 0.99 (95% CI: 0.82–1.20)] and lenvatinib [DCR_OR: 0.26 (95% CI: 0.05–1.33); PFS_HR: 0.99 (95% CI: 0.81–1.22)]; and the following therapies for MTC: vandetanib 300 mg [objective response rate (ORR)_OR: 3.31 (95% CI: 0.68–16.22); vandetanib 150 mg ORR_OR: 0.60 (95% CI: 0.16–2.33)]; and cabozantinib [ORR_OR: 85.32 (95% CI: 5.22–1395.15)]. Serious side effect (SE) analysis per organ/system demonstrated a varying MKI SE profile across both RR-WDTC and MTC diagnoses, more commonly involving metabolic/nutritional disorders [OR: 2.07 [95% CI: 0.82–5.18)] and gastrointestinal SE [OR: 1.63 (95% CI: 1.0–2.66)]. This network meta-analysis on advanced and/or metastatic TC points towards a higher efficacy of lenvatinib in RR-WDTC. The included MKIs exhibit a varying SE profile across different organs/systems favoring a patient-tailored approach with the anticipated toxicities guiding clinicians’ decisions.
Keywords: multikinase inhibitors; advanced/metastatic thyroid cancer; network meta-analysis